Brazilian uprising - Rafael Gonçalves de Almeida; Matheus da Silveira Grandi (PlaNext, 2015)
Brazil experienced, in June of 2013, the largest popular demonstrations in its recent history —an event that has been called the June Journeys. In this paper, we briefly address briefly the processes of spatial diffusion and dispersion observed during these journeys. We then reflect on how these processes relate to a politics of identity, and the strategies used by protesters to differentiate themselves from other groups, and by the State to classify the protesters in order to guide the use of police repression. Identity can, therefore, group individuals around a common struggle using as reference the location of the demon-stration as ‘spaces of identity reference’, but can also play an important role in the reproduction of dominant power relations by creating mechanisms with which to legitimate punitive action. The ‘vandal’ is, then, understood as the identity constructed to allow the transition from an indirect regulation to a mode of violent intervention. We conclude the paper by emphasising how both of these processes highlight the role of the politics of identity on this recent series of demonstrations in Brazil.